2015
DOI: 10.1002/bkcs.10207
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study on Reactions of O‐Y‐substituted Phenyl Thionobenzoates with Quinuclidine: Factors Governing Reactivity and Reaction Mechanism

Abstract: Second‐order rate constants (k quin) for the reactions of O‐Y‐substituted phenyl thionobenzoates (3a–3i) with quinuclidine have been measured spectrophotometrically. Comparison of k quin with the rate constants reported previously for the corresponding reactions with benzylamine (k BzNH2) has revealed that quinuclidine is less reactive than benzylamine toward 3a–3i although the former is 2.1 pK a units more basic than the latter. Steric hindrance exerted by quinuclidine has been suggested to be responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…Thus, one might suggest that the reactions of 1a with quinuclidines proceed through a stepwise mechanism in which expulsion of the leaving group occurs in the RDS on the basis of the linear Brønsted‐type plot with β nuc = 0.89. However, this idea is inconsistent with our previous report that quinuclidinolysis of O ‐Y‐substituted phenyl thionobenzoates including 1a proceeds through a concerted mechanism on the basis of the kinetic result that the Yukawa–Tsuno plot exhibits an excellent linear correlation with ρ Y = 0.96 and r = 0.51 …”
Section: Resultscontrasting
confidence: 95%
See 4 more Smart Citations
“…Thus, one might suggest that the reactions of 1a with quinuclidines proceed through a stepwise mechanism in which expulsion of the leaving group occurs in the RDS on the basis of the linear Brønsted‐type plot with β nuc = 0.89. However, this idea is inconsistent with our previous report that quinuclidinolysis of O ‐Y‐substituted phenyl thionobenzoates including 1a proceeds through a concerted mechanism on the basis of the kinetic result that the Yukawa–Tsuno plot exhibits an excellent linear correlation with ρ Y = 0.96 and r = 0.51 …”
Section: Resultscontrasting
confidence: 95%
“…We have recently reported that the Brønsted‐type plot for the reactions of quinuclidine with a series of O ‐Y‐substituted phenyl thionobenzoates ( 1a–1i ) is linear with β lg = −0.37, which is typical for reactions reported previously to proceed through a stepwise mechanism, with formation of an intermediate being the RDS. However, the Hammett plot correlated with σ o constants has exhibited highly scattered points . In contrast, the Yukawa–Tsuno plot for the same reactions has resulted in excellent linearity ( R 2 = 0.9991) with ρ Y = 0.96 and r = 0.51 .…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations